Congenital diaphragmatic hernia: A 4-year experience in a single centre - Ozdogan Tutku; Durakbasa Cigdem; Mutus Murat; Iscen Mavisen (Wolters Kluwer Medknow Publications, 2010)
Background: This study aimed to evaluate congenital diaphragmatic hernia (CDH) patients in our department during a 4-year period. Patients and Methods: A retrospective study of 10 cases of CDH patients managed in the Neonatology and Pediatric Surgery Units of Goztepe Teaching Hospital from 2000 to 2004. Results: The mean birth weight of the patients was 2,600 g and the mean gestational age was 37.6 weeks. The mean admission time for the patients was 10.4 h. The mortality rate was 50%, comprising two deaths before operation and one during operation. The surviving infants followed for 1 year are free of any symptoms and complications. Conclusion: Conventional ventilation is an other treatment modality, especially in order to gain time before surgical operation for newborns with CDH.